Role of Weak Interactions and Steric Effect in Chemosensing Using Cyclodextrins - Koyuncu, Ayfer; Çiftçi, Fatih (Springer, 2025)
Cyclodextrins (CDs), a family of cyclic oligosaccharides, have garnered significant attention in chemosensing applications due to their unique ability to form inclusion complexes with various guest molecules. The hydrophobic inner cavity and hydrophilic outer surface of CDs enable selective encapsulation of various guest molecules, including small organic compounds, ions, and biological entities. This selective binding is primarily driven by weak non-covalent interactions, such as hydrogen bonding, van der Waals forces, hydrophobic interactions, and occasionally π-π stacking. These interactions make CDs an excellent molecular scaffold for designing chemosensors with enhanced sensitivity and specificity. Chemosensing applications utilizing CDs exploit their ability to act as molecular hosts, which modulate optical or electrochemical signals upon guest binding. For example, CDs are often incorporated into fluorescence-based sensors, where the inclusion of a target molecule within the CD cavity can lead to changes in fluorescence intensity or wavelength. Similarly, CDs are used in electrochemical sensors to detect redox-active species by facilitating the selective binding of analytes in complex sample matrices. CDs also enhance the detection of pollutants, drugs, or biomarkers in environmental, clinical, and industrial settings through such interactions. A critical factor influencing the efficiency of these chemosensing systems is the steric effect, which refers to the spatial arrangement and size of guest molecules relative to the CD cavity. The three main types of cyclodextrins such as α-CD, β-CD, and γ-CD differ in cavity size (with 6, 7, and 8 glucopyranose units, respectively), allowing for selective encapsulation based on the size and shape of the guest. Steric hindrance can either enhance or hinder the inclusion process depending on the degree of fit between the host and guest. Larger or irregularly shaped molecules may experience steric clashes with the CD cavity walls, reducing binding affinity or preventing complexation altogether. On the contrary, a well-fitting guest molecule can lead to strong binding and high selectivity. Moreover, the functionalization of cyclodextrins with various chemical groups can modulate their steric and electronic properties, enabling fine-tuning of guest selectivity and sensor performance. For instance, the introduction of bulky substituents or charged groups can create additional steric barriers or enhance electrostatic interactions, respectively, thus influencing the strength and specificity of binding. These steric considerations are crucial in designing CDs for chemosensing applications, as they govern both the recognition and transduction mechanisms underlying sensor functionality. In conclusion, cyclodextrin-based chemosensors are versatile platforms that rely on weak non-covalent interactions and steric effects to achieve high selectivity and sensitivity in the detection of a wide range of analytes. By optimizing the size and functionalization of CDs, researchers can develop advanced chemosensors with tailored properties for applications in environmental monitoring, biomedical diagnostics, and industrial processes. This chapter explains the above-mentioned in a comprehensive manner. Graphical Abstract The image is a scientific figure illustrating various chemical structures and interactions. At the center, there is a 3D representation of a molecular complex on a platform, surrounded by chemical structures and diagrams. Labels include "Hydrophobic interactions and cavity," "Inclusion complex," "Hydrophilic interactions," "Van der Waals forces," and "Steric effects." The figure includes hexagonal and circular molecular diagrams, with arrows indicating interactions. The background is light blue, enhancing the visibility of the structures and text. The graphical abstract illustrating the role of weak interactions and steric effects in chemosensing using cyclodextrins.